1994
DOI: 10.1073/pnas.91.18.8675
|View full text |Cite
|
Sign up to set email alerts
|

Using bulked extremes and recessive class to map genes for photoperiod-sensitive genic male sterility in rice.

Abstract: Photoperiod-sensitive genie male sterile (PS-GMS) rice has a number of desirable characteristics for hybrid rice production. In this study we made use of a published rice genetic linkage map to determine the locations ofPSGMS genes and we have characterized the effects of these genes on sterility by using molecular markers. A two-step approach was designed for maing the genes: (i) Identifying possible PSGMS gene-containig chromosome regions with bulked DNA from extreme fertile and extreme sterile plants of a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
181
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(194 citation statements)
references
References 10 publications
(10 reference statements)
10
181
0
1
Order By: Relevance
“…This locus was designated as pms3 (Mei et al, 1999a;1999b), and was delimited into a 28.4-kb interval on chromosome 12 (Lu et al, 2005). In contrast, the fertility trait of 32001S, an indica PGMS line also derived from Nongken 58S, displays a two-locus segregation pattern in the progeny resulting from a cross with the indica cultivar Minghui 63 (Zhang et al, 1994), indicating that the fertility trait segregation is dependent on the genetic backgrounds of the materials used in the crosses. The two loci were designated as pms1 and pms2, and were localized on chromosomes 7 and 3, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This locus was designated as pms3 (Mei et al, 1999a;1999b), and was delimited into a 28.4-kb interval on chromosome 12 (Lu et al, 2005). In contrast, the fertility trait of 32001S, an indica PGMS line also derived from Nongken 58S, displays a two-locus segregation pattern in the progeny resulting from a cross with the indica cultivar Minghui 63 (Zhang et al, 1994), indicating that the fertility trait segregation is dependent on the genetic backgrounds of the materials used in the crosses. The two loci were designated as pms1 and pms2, and were localized on chromosomes 7 and 3, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…LOC_Os07g12130, 12140, 12160, 12170, and 12240 were used as the candidate genes, and ubiquitin as a control in our experiment PTGMS varieties derived from Nongken 58S was controlled by two recessive genes. The PGMS genes of the line 32001S consist of the two gene loci (pms1 and pms2), of which the pms1 gene was located on chromosome 7 (Zhang et al, 1994;Mei et al, 1999b;Liu et al, 2001;Lu et al, 2005), and another pms3 gene on chromosome 12 (Lu et al, 2005). Localization studies showed that the TGMS genes from different sources may be located in different chromosomes.…”
Section: Genetic Diversity Of Ptgms Ricementioning
confidence: 99%
See 2 more Smart Citations
“…The SSR marker umc1331 was considered as a potential linkage marker of the RsrR gene. Then the linkage relationship was checked and confirmed by analyzing with 150 susceptible F 2 individuals (Zhang et al 1994). Results indicated that umc1331 was really linked to the resistant gene RsrR (Fig.…”
Section: Ssr Analysismentioning
confidence: 99%